2000
DOI: 10.1021/ma9911849
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Look at Models for Polymer Entanglement

Abstract: Several apparently contradictory models predicting critical conditions for chain entanglement in flexible polymers have appeared in recent years. Some models predict entanglement molecular weight to increase, and others to decrease, with chain stiffness. Literature data are used here to compare model predictions. An inverse correlation between characteristic ratio and segmental aspect ratio is found, allowing the contradiction to be resolved. In flexible chains, it is found that the aspect ratio of a Kuhn step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 22 publications
1
72
0
1
Order By: Relevance
“…The average end-to-end distance R e of PEO polymer chains with M w = 43 000 g mol −1 can be calculated to be 19 nm. 24 The melting temperature of bulk PEO is 338 K. The PEO films were placed onto the AAO templates in order to carry out the infiltration by the "precursor film" infiltration method. 25,26 In this method, a polymeric liquid precursor film spreads over the whole surface of the AAO template, pore walls included.…”
Section: Infiltration Of Poly"ethylene Oxide… Into the Nanoporesmentioning
confidence: 99%
“…The average end-to-end distance R e of PEO polymer chains with M w = 43 000 g mol −1 can be calculated to be 19 nm. 24 The melting temperature of bulk PEO is 338 K. The PEO films were placed onto the AAO templates in order to carry out the infiltration by the "precursor film" infiltration method. 25,26 In this method, a polymeric liquid precursor film spreads over the whole surface of the AAO template, pore walls included.…”
Section: Infiltration Of Poly"ethylene Oxide… Into the Nanoporesmentioning
confidence: 99%
“…Notably, the most successful of them are based on similar [38][39][40][41] ideas. A good correlation with polymer melt data is provided by the packing length 42 model, which is based on the conjecture of Lin, 43 and Kavassalis and Noolandi.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of entanglement for the ith component in the blend (N i ) is given by the equation (13) where M i is the molecular weight of the ith component. Therefore, M e of the ith component in the blend can be determined by…”
Section: Determination Of Individual Molecular Parametersmentioning
confidence: 99%
“…Although Aharoni's chain stiffness parameters and M e 's of a large number of polymers support this relationship, 9 it was shown later by Fetters et al 12 that the relation C ϱ ϰ N e 0.5 is imprecise because N e increases with temperature while C ϱ can either remain constant, decrease, or increase. Various polymer entanglement models were reviewed by Heymans,13 who demonstrated that the Fetters 12 and the ColbyRubinstern 14 models are applicable. In the present work, the Fetters model, which relates plateau modulus to packing length, from which ͗R 2 ͘/M w can be estimated, will be preferred for its ease of use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation